Attachment, authenticity, and honesty dispositional and experimentally induced security can reduce self-and other deception. [article]. - Gillath, Omri
Attachment security is hypothesized to promote authenticity and sincerity, or honesty, whereas insecurity is hypothesized to increase various forms of inauthenticity and dishonesty. The authors tested these ideas in 8 studies of dispositional and situational attachments insecurities and their influence on in authenticity and dishonesty. The first 4 studies showed that authenticity is related to scoring low on the 2 dimensions of dispositional attachment insecurity-anxiety and avoidance- and that these 2 dimensions are associated with different aspects of inauthenticity . The first set of studies also showed that conscious and unconscious security priming increased state authenticity (compared with neutral or insecurity priming). The last 4 studies showed that attachment insecurity is related to dishonesty(lying and cheating) and that security priming reduces the tendency to lie or cheat and does so more effectively than positive mood priming. Implications for understanding the role of authenticity and inauthenticity in various relationship contexts are discussed. -- (from the author)
Keywords: Attachment security; Authenticity; Honesty; Lying; Cheating